DIGITALISASI PENCATATAN TRANSAKSI KEUANGAN PADA PELAKU USAHA MIKRO DAN KECIL KOTA TANGERANG - Simorangkir Rona Tumiur Mauli Carolin (COMVICE: Journal Of Community Service, 2023)
Small and Medium Enterprises (SMEs) are one of the businesses that can support economic activities. However, there are still many SMEs that handle their business traditionally and are not able to submit their business financial reports correctly. The aim of implementing this Community Service activity is to help UKM owners in Tangerang City to be able to monitor the condition of their business through financial reports easily and efficiently. This PKM activity involves the Department of Industry, Trade, Cooperatives and SMEs in the city of Tangerang. The fostered partners involved in this activity are micro business owners spread across 13 sub-districts in the city of Tangerang. Activities were carried out intensively online in October 2023. This PKM activity was successful and received a positive response from the fostered partners. It is hoped that this PKM activity will not stop there, but can continue with other training.